The Association Between Firm Risk and Wealth Transfers Due to Inflation - Rozeff, Michael S. (Journal of Financial and Quantitative Analysis, 1977)
The net monetary position of a firm, defined as the nominal value of its monetary assets minus the nominal value of its monetary liabilities, partly determines the wealth transferred to (or from) the firm's owners when unanticipated price level change occurs. Price level change (a random variable) is defined as unanticipated when assessments of (the moments of) its probability distribution are systematically incorrect or biased. During unanticipated inflation, which conventionally means an underestimate of the expected value of the distribution of price level change, the real dollar returns of net monetary debtor firms are enhanced—the unforeseen honoring of debt contracts in dollars of lower purchasing power is a wealth transfer to the firm's owners from the firm's creditors. Conversely, real returns of net monetary creditor firms suffer during unanticipated inflation and gain during unanticipated deflation.